Återhämtningen och stödets betydelse för en hälsofrämjande arbetsmiljö - Näslund, Jennie; Wonkavaara, Camilla (2016)
The purpose of this study was to investigate how the workers possibilities for support and recovery on workplaces and what we could do to contribute to recovery from a statutory perspective. The study was a quantitative and qualitative study, a so called mixed method with alignment of the descriptive where the data collection were made with paper surveys on the workplaces. It was an open study which contained three workgroups with men and women in the age of 22 to 65. The study took place on different locations in northern Sweden and were directed at people working within social services and elderly care. 59 respondents answered the survey. The data analysis of the results were made using the most relevant findings from the possibility for support and recovery on workplaces. The collected data were first transferred to Microsoft Excel and later on transferred to graphs. The result showed that the possibility to recovery is low due to high workload and not enough time for breaks. The respondents were experiencing high load due to the lack of possibilitíes to work in a calm environment. For the respondents to have a good work environment they felt that they needed more time both for breaks and for their duties. They also felt that they needed a calm and peaceful place to go to for food or coffee breaks so they can recover better during the worktime. The respondents felt that they have good support from managers and work associates. Health guiders can greatly benefit from the study as they can work with health promotion by working with recovery on workplaces with support from the new law of working environment. Validerat; 20160615 (global_studentproject_submitter)